A model of factors influencing knowledge management system adoption among academicians in Nigeria universities - Salami, Ahmed Babajide (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
Higher Education Institution (HEI)/Universities are we known as the knowledge hub where knowledge is acquired and shared among all. In order for the Nigerian universities to fully realize its knowledge management related objectives, there will be a requirement of a knowledge management system to support it. The universities also face various challenges regarding this system, including whether or not to adopt it, whether users would accept to work with it. Therefore, adoption of knowledge management systems occurs in both organizational level, and individual level. The objective of this study is to investigate the factors affecting the adoption of Knowledge management system in Nigeria Universities. This study investigates the factors influencing Knowledge management system adoption from the academicians' perspective. This study identified factors of 1) Organization (Structure, Government support, Culture, and organizational infrastructure), 2) Individual (Knowledge, Personal innovativeness, experience, and attitude), 3) Management Support (training, management initiatives and management) and 4) technology (trialiability, compatibility, visibility and complexity) and their influence on KMS system usage. An explanatory quantitative method design using survey as the data collection methodology was used as the research design for the study. A survey using questionnaire provided quantitative descriptions of the sample within the chosen population through a data collection. Analysis for this problem required a causal, non-contrived field study employing multiple regression analysis. Data was collected using a 28 item survey distributed to academicians from a variety of universities in Nigeria. The study in particular found that individual and management support factors play a role on the adoption of KMS in Nigeria more than organizational and technological factors and the study shows influences of adoption among academicians within the institutions of higher learning. The finding of the study paves a way for other research that will involve the participation of developed countries as well. This allow the intended future implementation of KMS technology to identify the factors most especially management support and Individual factor as tools in measuring the importance of KMS and Researchers will benefit from the KMS adoption model and also the findings attached to the research.